Three major crises and Asian emerging market informational efficiency: A case of Pakistan Stock Exchange-100 Index - Bahrawar Said; Shafiq ur Rehman; Muhammad Wajid Raza (Journal of Risk and Financial Management, 2022)
Periods of economic turmoil distort the ability of stock prices to reflect the available information. In the last three decades, emerging markets experienced numerous crises. The major three of them are the Asian Financial Crisis (1997-1998), Global Financial Crisis (2007-2009) and Global Pandemic Crisis (2020-2022). The nature, intensity and duration of these crises differ significantly. This study investigates the impact of these varying natures of crises on the level of informational efficiency. The empirical evidence is based on the emerging stock market of Pakistan. Index-level data are collected from Pakistan Stock Exchange-100 Index for the period 1995-2022. The rebalancing is done each year to ensure that the final sample is composed of only 100 stocks with the highest market capitalization. The results based on the Variance Ratio (VR) test show that informational efficiency is time-varying. Among all the three crises, informational efficiency deters more in the COVID-19 pandemic, albeit the market efficiency recovers soon. This implies that the arbitrage opportunity is marginal in crisis periods, while investors prefer to invest in post-crisis periods. Finally, our results reveal that among all the crises, investors were more informed in the Global Financial Crisis. Investors must keep a close eye on market regimes for designing investment solutions.
Keywords: G01; G11; G12; G14; 650; Asian Financial Crisis (AFC); Global Financial Crisis (GFC); Global Pandemic Crisis (GPC); market efficiency; PSX-100 Index